Early Learning for Aboriginal Children: Past, Present and Future and an Exploration of the Aboriginal Head Start Urban and Northern Communities Program in Ontario - Mashford-Pringle, Angela (First Peoples Child & Family Review, 2012)
This article provides some key findings from a case study of the Aboriginal Head Start Urban and Northern Communities (AHSUNC) Program in Ontario. Some of the key findings were improved self-reported health status, commitment to cultural and linguistic revitalization, reduced tobacco use, improved knowledge of healthy living practices among Aboriginal children and their families. The number of off-reserve Aboriginal children that can experience AHSUNC is limited by funding and availability of space and human resources. The participants in this study have shown improved knowledge, interaction with their children, and increased understanding of their biculturedness within Ontario. Therefore it is important to increase this funding and continue to conduct research with AHSUNC projects across Ontario to document and highlight their successes as a model for other provinces/territories and early childhood programs.